COULD THE RESIZING OF MANAGEMENT ACCOUNTING IMPROVE THE FINANCIAL PERFORMANCE OF NATIONAL SOCIETIES? - VERONICA CATARGIU; BOGDAN RĂVAŞ (Annals of the University of Petrosani: Economics)
The specific dynamics of the economy under the influence of the technical-scientific progress has brought new problems to the economic research, problems that national companies and not only are them facing and which are requiring more and more the attention of the specialists in the domain of costs research. We therefore started from the premise that the economic activity generating expenses within the national companies include a suite of profound qualitative and structural transformations which decisively depend on the scientific research aiming at a correct theoretical-methodological substantiation of the strategic decisions to be taken under this category of economic entities.